Los espiónidos (Polychaeta: Spionidae) del Golfo de California y Golfo de Tehuantepec, México - Hernández-Alcántara, P; González-Ortíz, L; Solís-Weiss, V (Revista de Biología Tropical, 1994)
The composition and distribution of the Spionidae, one of the most diverse, abundant and frequent polychaete families in the continental shelf of the Mexican Pacific was studied in the Gulfs 01' California and Tehuantepec. Thirty seven stations were sampled in the former and 30 in the latter. A total of 5153 organisms in 12 genera and 27 species were determined. The spionids were better represented in the central-eastern region in the Gulf of California and to the west of Salina Cruz, in the Gulf of Tehuantepec, in depths ranging from 60 to 100 m. In both areas, the dominant species was Parapríonospio pinnata, a cosmopolitan species, distributed practically along the entire study area and representing 75% and 86% of the organisms found in the Gulfs of California and Tehuantepec respectively. The spionids, basically represented by species with Amphiamerican or extended geographic distribution, represent 64% of the organisms from both gulfs.